2019
DOI: 10.1007/s12678-019-00570-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Energy Conversion from Direct Oxidation of Glucose on Active Electrode Materials

Abstract: Electrochemical behavior of carbon supported platinum and gold-based catalysts towards glucose oxidation and oxygen reduction reaction were investigated separately in alkaline medium before implementing the glucose/O2 fuel cell with the best anode and cathode catalysts. These electrode materials, prepared from a surfactant-free synthesis approach, were then used in low metal loadings in a fuel cell operating in alkaline medium which can be easily removed on resin for analyzing all the reaction products, as any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The strong peak near 168.35 eV can also be attributed to some oxidized sulfur, which usually forms at the edge of graphene. Due to the spin-orbit coupling in the sulfur atom, the first two peaks were related to the 2p 3/2 (161.44 eV) and 2p 1/2 (162.6 eV) of thiophene S [ 42 ]. The remaining peak C-SOx-C was caused by the sulfur element in sulfur oxide.…”
Section: Resultsmentioning
confidence: 99%
“…The strong peak near 168.35 eV can also be attributed to some oxidized sulfur, which usually forms at the edge of graphene. Due to the spin-orbit coupling in the sulfur atom, the first two peaks were related to the 2p 3/2 (161.44 eV) and 2p 1/2 (162.6 eV) of thiophene S [ 42 ]. The remaining peak C-SOx-C was caused by the sulfur element in sulfur oxide.…”
Section: Resultsmentioning
confidence: 99%
“…We previously examined the electrochemical properties by cyclic voltammetry (CV), and electrocatalytic performance by the direct glucose fuel cell in alkaline medium [39]. So, the characterization was not performed herein.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…More conductive material such as graphene layer was used as substrate for electrodepositing Au and Pt nanocatalysts for glucose oxidation [38]. BAE method was also performed to disseminate catalysts nanoparticles on reduced graphene oxide (rGO) [39]. The latter approach method is a surfactant-free synthesis based on the anion exchange between the bromide and the chloride anions before reduction by sodium borohydride.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose electrooxidation (GAEO) to gluconic acid reactions are given as follows [23,24] (3) The development of anode catalysts with high GAEO activity is crucial for the commercialization of the direct glucose fuel cell. Hence, the anode catalyst performance of Fe 15 Pt 85 [25], Ni-Fe [26], Ni-Co [27], Au [28], Pt [29], G-ITO [30], AgNi [31], Pd [32], FeCo 2 O 4 [33], and Pd-Au [34] nanocatalysts have been investigated for direct GA fuel cells (DGFC). For instance, Chai et al reported that Pd 3 Cu-B/C nanocatalyst synthesized by a simple aqueous phase approach method had high GAEO activity and stability for GAEO reaction in fuel cell [35].…”
Section: Introductionmentioning
confidence: 99%